Industry peer information and the equity valuation accuracy of firms emerging from Chapter 11 - FANG, Bingxu (Institutional Knowledge at Singapore Management University, 2025)
Valuation plays a central role in determining Chapter 11 reorganization outcomes. However, obtaining accurate valuation estimates of reorganized firms is challenging because of limited firm-specific market-based information and the oft-conflicting incentives of claimholders. We examine the role of industry peer information in reducing misvaluations and its implications for unintended interclaimant wealth transfers and postreorganization performance. First, we find that the availability of relevant industry peer information is negatively associated with equity valuation errors for firms emerging from Chapter 11. Cross-sectional results suggest that the relation between industry peer information and valuation errors varies substantially with debtors’ information environment and case characteristics. Second, we find that industry peer information quality is associated with better ex post financial performance of emerged firms because of lower overvaluation. Finally, we document the role of industry peer information in substantially reducing the frequency and magnitude of unintended wealth transfers between claimants arising from equity valuation errors.